NGHIÊN CỨU TÁC DỤNG CỦA BĂNG NANO BẠC LÊN QUÁ TRÌNH ĐIỀU TRỊ VẾT THƯƠNG BỎNG - Dung, Trần Thị Ngọc; Châu, Nguyễn Hoài; Hiền, Đào Trọng; Phượng, Nguyễn Thúy; Bưu, Ngô Quốc; Tiến, Nguyễn Gia (Vietnam Journal of Science and Technology, 2012)
Silver was known as a strongest antimicrobial element in the nature, moreover in the nano-sized form it can modulate the wound healing process by developing pro-healing or inhibiting pro-inflammatory cytokines, resulting in accelerated wound recovery and improved cosmetic appearence. This report represents some results of using nanosilver-coated wound dressings for therapeutic treatment of burns. The dressings were manufactured by immersing non-woven fabric material into a nanosilver solution of concentration of 500 mg/l with an average size of 20 – 25 nm, which was produced by aqueous molecular solution method. The healing effect of the tested dressing was studied through the comparison with silver sulfadiazine-coated one. The experimental data obtained showed that nanosilver-coated dressing heals burns with accelerated healing and without scars, much better than silver sulfadiazine-coated dressing.